Phosphite applications induce molecular modifications in potato tuber periderm and cortex that enhance resistance to pathogens - Olivieri, Florencia Pia (2012)
Phosphite (Phi) compounds are salts derived from phosphorous acid. These compounds have the ability to protect plants against different pathogens. The aim of the present research was to assess the effect of Phi compounds on components of potato tuber periderm and cortex and to assess their effects on pathogen resistance in the postharvest stage. In a series of field experiments, potassium phosphite (KPhi) was applied to seed potato tubers and foliage. After harvest, several variables were analyzed in tubers obtained from these plants. An increase in pectin content was observed in both periderm and cortex tissue in tubers originating from KPhi-treated plants. After wounding and infection with Fusarium solani, a higher amount of pectin accumulation in cortical tissues was observed in tubers following treatment with KPhi. The content and/or activity of polygalacturonase and proteinase inhibitor also increased in tubers from KPhi-treated plants. A new isoform of chitinase was detected in the tuber periderm of treated plants. These results suggest that KPhi applied to seed tuber and foliage induces defense responses in tuber periderm and cortex and that these reactions are associated with structural and biochemical changes in these tissues.